E-business and telecommunications : 12th International Joint Conference, ICETE 2015, Colmar, France, July 20-22, 2015, Revised selected papers /: 12th International Joint Conference, ICETE 2015, Colmar, France, July 20-22, 2015, Revised selected papers. (2016) - Unknown
No abstract available